Revitalisasi Fungsi Masjid Jami’ Al-Istigfar sebagai Pusat Pemberdayaan Masyarakat Bidang Sosial Era Modern Di Kelurahan Tondo Kota Palu - Maulidiyah, Nur; Adam, Adam; Hasriani, Hasriani (Jurusan Pengembangan Masyarakat Islam Fakultas Dakwah dan Komunikasi Islam, UIN Datokarama Palu., 2025)
The revitalization of the mosque’s function involves a paradigm shift from viewing the mosque solely as a place of worship to recognizing it as a center for community empowerment. As a hub for empowerment, the mosque plays a crucial role in shaping, advancing, and strengthening its surrounding community. This study formulates three main research questions: (1)What is the role of the mosque in social community empowerment in the modern era? (2) What are the effective strategies for revitalizing the mosque’s function as a center of community empowerment? (3) What are the outcomes of the revitalization efforts at Jami’ Al-Istigfar Mosque? The objective of this study is to analyze the mosque’s role in social community empowerment in the modern era, to identify strategies for revitalizing the mosque’s function, and to assess the results of these efforts. This study employs a qualitative research design with a descriptive approach. Two main types of data are utilized: primary and secondary data. Data collection techniques include observation, in-depth interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The results of the study indicate that the mosque plays a significant role in community empowerment, particularly in the social domain. The mosque is not only a place of worship but also serves as a center for social activities that foster community interaction, develop individual capacities, and improve overall community welfare.